A study proposal on short term outcome and prognosis of primary and delayed fulguration in posterior urethral valve - T., Jeevarathi; Vadivelu, Gomathi (International Surgery Journal, 2020)
Background: Posterior urethral valve (PUV) is the most common cause of lower urinary tract obstruction in male neonates. The incidence is 1 in 4000, 1 in 7500 births PUV occur exclusively in males. This disease has a broad spectrum of presentations. They may present at any age during childhood and may vary from ascites in the neonate to renal failure in infants and only minor voiding dysfunction in an older child. Urinary tract infection is common at all ages. The objectives of the study were to assess the impact of primary impaction on short term outcomes and to assess the outcome of diversion and delayed fulguration. Methods: This retrospective study was conducted at the Pediatric Urology outpatient department (OPD) at the Institute of Child Health and Hospital for Children, Madras Medical College, Chennai including the patients who attended the pediatric surgery from August 2008 to December 2011. Results: In the current series, the incidence of renal insufficiency in patients with urosepsis was 45%. Recurrent urosepsis >3 episodes in a year (fever with urine culture showing infection) primarily due to poor patient compliance lead to progressing pyelonephritis and nephron damage and plays an important role in the outcome of these children. Conclusions: The incidence of renal insufficiency in children with posterior urethral valves in this series was 38% (30-45%) with an average follow up 3 years. Several factors were important in prognosticating the progression towards renal insufficiency and bladder dysfunction. Urodynamics is of immense help in cases having symptoms despite good stream. The use of anticholinergic for abnormal urodynamics gives encouraging results.